2023
DOI: 10.3390/life13061316
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the GCLC Gene Are Novel Genetic Markers for Susceptibility to Psoriasis Associated with Alcohol Abuse and Cigarette Smoking

Ekaterina Efanova,
Olga Bushueva,
Roman Saranyuk
et al.

Abstract: The aim of this pilot study was to investigate whether single nucleotide polymorphisms (SNP) in the gene encoding the catalytic subunit of glutamate cysteine ligase (GCLC) are associated with the risk and clinical features of psoriasis. A total of 944 unrelated individuals, including 474 patients with a diagnosis of psoriasis and 470 healthy controls, were recruited for the study. Six common SNPs in the GCLC gene were genotyped using the MassArray-4 system. Polymorphisms rs648595 (OR = 0.56, 95% CI 0.35–0.90; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…External exposome factors can also induce a psoriasis flare indirectly by modifying inner exposome factors (for example, oxidative stress triggered by tobacco [ 27 ]) as well as direct contributions to the pathogenesis pathways of psoriasis (nicotine stimulates the increased secretion of various cytokines) [ 28 ]. External exposome factors include environmental pollution, alcohol and tobacco abuse, as well as stress and sleep deprivation, diet, and lifestyle habits.…”
Section: Introductionmentioning
confidence: 99%
“…External exposome factors can also induce a psoriasis flare indirectly by modifying inner exposome factors (for example, oxidative stress triggered by tobacco [ 27 ]) as well as direct contributions to the pathogenesis pathways of psoriasis (nicotine stimulates the increased secretion of various cytokines) [ 28 ]. External exposome factors include environmental pollution, alcohol and tobacco abuse, as well as stress and sleep deprivation, diet, and lifestyle habits.…”
Section: Introductionmentioning
confidence: 99%
“…Efanova et al’s work [ 13 ] proved, for the first time, the connection of GCLC gene’s polymorphism (which is involved in glutathione metabolism) with the development of a widespread skin disease, such as psoriasis. The authors demonstrated significant sex-specific features of the association of the GCLC gene’s genetic variant with the disease, the modifying effect of smoking/alcohol consumption on these associations and established significant correlations of the considered genetic determinants with various clinical signs, such as the disorder’s age of onset, the psoriatic triad and the nature of the target organ’s lesion—the skin.…”
mentioning
confidence: 99%